Flowers and mycorrhizal roots – closer than we think?. (June 2015) - Nouri, Eva; Reinhardt, Didier
Highlights Surprising overlaps between root symbiosis and pollen development. Genetic and transcriptomic overlaps between arbuscular mycorrhiza and pollen development. Lipid polyester pathway is involved in arbuscular mycorrhiza and pollen development.